Enhancement of antigen-specific CD4+ and CD8+ T cell responses using a self-assembled biologic nanolipoprotein particle vaccine. Issue 11 (13th March 2017) - Weilhammer, Dina; Dunkle, Alexis D.; Blanchette, Craig D.; Fischer, Nicholas O.; Corzett, Michele; Lehmann, Doerte; Boone, Tyler; Hoeprich, Paul; Driks, Adam; Rasley, Amy
Highlights: The model antigen OVA was covalently conjugated to nanolipoprotein particles (NLPs). NLP conjugation enhanced uptake of OVA by antigen presenting cells in vitro . NLP conjugation enhanced CD4 + and CD8 + T cell responses to OVA in vitro and in vivo . Abstract: To address the need for vaccine platforms that induce robust cell-mediated immunity, we investigated the potential of utilizing self-assembling biologic nanolipoprotein particles (NLPs) as an antigen and adjuvant delivery system to induce antigen-specific murine T cell responses. We utilized OT-I and OT-II TCR-transgenic mice to investigate the effects of NLP-mediated delivery of the model antigen ovalbumin (OVA) on T cell activation. Delivery of OVA with the TLR4 agonist monophosphoryl lipid A (MPLA) in the context of NLPs significantly enhanced the activation of both CD4 + and CD8 + T cells in vitro compared to co-administration of free OVA and MPLA. Upon intranasal immunization of mice harboring TCR-transgenic cells, NLPs enhanced the adjuvant effects of MPLA and the in vivo delivery of OVA, leading to significantly increased expansion of CD4 + and CD8 + T cells in lung-draining lymph nodes. Therefore, NLPs are a promising vaccine platform for inducing T cell responses following intranasal administration.